Impact of alcohol consumption on hyperuricemia and gout: a systematic review and meta-analysis - Weiwei Ma; Guancheng Ye; Yiying Liu; Weikang Sun; Xin Huang; Liekui Hu; Lingting Chen; Binbing Huang; Huanan Li; Huanan Li (Frontiers in Nutrition)
ObjectiveWith the rapid development of socio-economic conditions, the prevalence of hyperuricemia and gout has steadily increased, significantly impacting individuals’ quality of life. Among various dietary factors, alcohol consumption plays a crucial role in the onset and progression of these conditions. Despite its importance, systematic evaluations of the impact of alcohol consumption on hyperuricemia and gout remain limited. Therefore, this study conducts a meta-analysis to explore these effects, with a focus on the moderating roles of drinking frequency, gender, and other relevant factors.MethodsA comprehensive literature search was performed using PubMed, Embase, Cochrane, and Web of Science databases up to November 2024. Studies assessing the relationship between alcohol consumption and hyperuricemia or gout were rigorously screened and subjected to quality evaluation. Data extraction and statistical analyses were conducted using STATA 16.0 software. A dose–response analysis was performed to assess the relationship between drinking frequency and disease risk. Regression analysis explored the potential effects of gender, age, country, study type, type of alcohol, and diagnostic criteria on the outcomes.ResultsThe meta-analysis revealed that alcohol consumption significantly increases the risk of hyperuricemia and gout (OR = 1.69, 95% CI: 1.47–1.94; Z = 7.494, p < 0.05), indicating that drinkers have a 69% higher risk compared to non-drinkers. Egger’s test results (p = 0.317, p > 0.05) showed no significant publication bias, and sensitivity analyses confirmed the robustness of the findings after excluding individual studies. Dose–response analysis demonstrated a positive association between drinking frequency and the risk of hyperuricemia and gout. Regression analysis indicated that age, country, study type, type of alcohol, and diagnostic criteria had minimal effects on the results, while male were more vulnerable to alcohol-related hyperuricemia and gout than female.ConclusionThe findings from this meta-analysis confirm that alcohol consumption significantly elevates the risk of hyperuricemia and gout, with higher drinking frequency linked to increased risk. Additionally, male drinkers showed a substantially higher risk compared to female drinkers. These results provide strong evidence supporting the development of public health policies aimed at preventing and controlling hyperuricemia and gout, while offering a foundation for future in-depth research.Systematic review registrationThis study has been registered in the International Prospective Register of Systematic Reviews (PROSPERO). The registration details are as follows: CRD42024361042 (https://www.crd.york.ac.uk/PROSPERO/).